Making Waves: towards a harmonized approach for monitoring antimicrobial resistance in European surface waters - P. Krzeminski; C.U. Schwermer; M. Anglès d’Auriac; H. Bürgmann; H. Schmitt; J. Vierheilig; M. Gjeitnes; S.J. Moe; X. Bellanger; R. Carapeto García; P. Crespo Iniesta; C. Dagot; et al. (Water Research, 2026)

Successful outcome of open distal interphalangeal joint luxation in equids treated by surgical debridement without internal implants - L. C. Ferrari; E. V. P. Apolonio; S. L. de Oliveira-Gonçalves; A. L. A. Rambo; J. V. Bergamasco; J. M. Alonso; M. J. Watanabe; A. L. G. Alves (Veterinary Research Communications, 2026)
Introduction The distal interphalangeal joint (DIPJ) plays a crucial role in the function of the hoof and digit. Dislocations and subluxations in this region are rare and primarily of traumatic origin. Case Report This case report aims to describe two unusual cases of open DIPJ dislocation, including clinical presentation, diagnostic workup, treatment, and long-term follow-up. Both animals presented with open traumatic distal interphalangeal joint (DIPJ) luxation. In Case 1, the animal received initial care on the property 5 h post-trauma and presented with joint exposure and articular surface contact with the ground. In Case 2, the animal was referred to the veterinary hospital without prior care, 3 h post-trauma, but there was no contact of the articular surface with the ground. Both animals showed grade 5/5 lameness (AAEP). The animals underwent general anesthesia, joint lavage, regional intravenous perfusion with antibiotics, debridement of devitalized tissues, skin synthesis, and immobilization with synthetic casting. During immediate recovery and hospitalization, a grade 4/5 lameness persisted. Long-term radiographic control revealed the development of degenerative joint disease in both animals. After 3 and 2 years, respectively, animals 1 and 2 showed persistent lameness (grade 2/5) with an absence of local sensitivity. Conclusion The conservative treatment employed in these cases of open DIPJ luxation proved effective for the maintenance of the patients’ lives, and although the infectious pathological process invariably progressed to osteoarthritis, the evolution of the clinical conditions allowed for light exercise and maintenance of reproductive activity.

Bridging soil mapping units and digital soil mapping through probability-driven machine learning: an uncertainty-aware framework for soil class prediction in Antarctica - Rafael G. Siqueira; Cássio M. Moquedace; Márcio R. Francelino; Carlos Ernesto G.R. Schaefer; Roberto F.M. Michel; Daniela Schmitz; Flávia R. Ferrari; Caroline Delpupo; Eduardo O. Senra; Heitor P. Palma; Daniel N. Krum; Fábio S. de Oliveira; et al. (CATENA, 2026)

Aging impact on canine extracellular vesicles production, size, and miRNA content - Clara Luna Marina; Alexandra Mazer Greuel; Lucas de O. Las-Casas; Evilly Lopes-Gomes; Sabrina Simplício de Araújo Romero Ferrari; Marcio Lourenço Rodrigues; Flavia C. G. dos Reis; Anamélia Lorenzetti Bocca; Simoneide Souza Titze-de-Almeida; Fernando Francisco Borges Resende; Fabiano José Ferreira de Sant’Ana; Ricardo Titze-de-Almeida (Veterinary Research Communications, 2026)
Increasing life expectancy has been accompanied by a higher prevalence of age-associated conditions, underscoring the need to better understand biological mechanisms of aging and to identify accessible biomarkers. Extracellular vesicles (EVs) are lipid-bilayer vesicles that mediate intercellular communication by transporting proteins, lipids, and regulatory RNAs, including microRNAs (miRNAs). Here, we investigated whether the abundance, morphology, and molecular cargo of plasma-derived EVs differ between young and senior dogs. Blood samples were obtained from 24 clinically healthy dogs in Gama (Federal District, Brazil), and plasma EVs were isolated by sequential centrifugation, filtration through a 0.22 μm filter, and ultracentrifugation. EVs concentration and size distribution were assessed by nanoparticle tracking analysis (NTA), morphology by transmission electron microscopy (TEM), and cargo by quantification of total protein and sterols using commercial assays. In addition, we quantified miR-19b, miR-29c, miR-7, miR-155, and miR-21 by Real Time Quantitative Polymerase Chain Reaction (RT-qPCR). Senior dogs exhibited a lower plasma EV yield and greater size heterogeneity, with a higher proportion of larger EVs. Total protein and sterol content per starting plasma volume were reduced in the senior group; however, sterol normalized per EV was increased, consistent with compositional remodeling of circulating vesicles with age. Finally, EV-associated miRNA levels were reduced in senior dogs, particularly miR-19b and miR-29c. Collectively, these findings indicate that canine aging is associated with marked changes in plasma EV abundance, morphology, and cargo, indicating that EVs could represent a promising tool for investigating age-related disorders in dogs.

Circulating metabolites and fatty acids associated with ultra-processed food consumption: results from the EPIC study - Jessica Blanco-Lopez; Sahar Yammine; Joseph A. Rothwell; Mathilde His; Carine Biessy; Pekka Keski-Rahkonen; Bernadette Chimera; Inarie Jacobs; Aline Al Nahas; Emine Koc Cakmak; Oliver Robinson; Fernanda Morales Berstein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Challenges in estimating wolf population size using spatial count models and camera trap data - M.V. Boiani; P. Dupont; R. Bischof; O. Friard; F. Bisi; G. Bombieri; S. Calderola; S. Carolfi; C. Chioso; U. Fattori; P. Ferrari; S. Filacorda; et al. (Biological Conservation, 2026)

Sociality and nesting strategy account for non-random associations between bees and their parasitic dipterans - C. Polidori; A. Ferrari (Insectes Sociaux, 2026)
Bees (Apoidea: Anthophila) are recorded as common hosts of a diverse array of parasitic Diptera species, but information is widely scattered across the literature, limiting our knowledge of global bee-dipteran association patterns. Here, we retrieved published information on 453 bee-dipteran associations to test the role of life-history traits of hosts and parasites on such patterns. The 13 families and 37 genera of Diptera associated with bees are unevenly distributed across bee families within a specialized and modular network. The family Apidae was the most associated with parasitoids of adults, Colletidae were the most attacked by nest-entering larval parasitoids, Apidae and Megachilidae were the most attacked by non-nest-entering larval parasitoids, and cleptoparasites were more frequently observed attacking Andrenidae and Halictidae nests. The number of parasitic strategies, but not the richness of Diptera, was higher in fossorial species and both weakly depended on bee phylogeny. However, when considered singularly, the four parasitic strategies ((i) parasitoids of adults; (ii) nest-entering larval parasitoids; (iii) non-nest-entering larval parasitoids; and (iv) cleptoparasites) yielded moderate phylogenetic signals. Fossorial species were more associated with cleptoparasites, while the association rate of non-nest-entering larval parasitoids was higher in aerial-nesting bee species and in solitary bee species. In addition, fossorial bee species were found to be more specialised in their associate dipteran fauna. Despite the uneven distribution of studies across bee genera, our results suggest that these associations emerged through co-evolutionary processes, during which dipterans specialized and optimized their parasitic strategies based on the ecological traits of their host bees.

Incorporation of dose-rate effects into the BIANCA biophysical model and application for space radiation risk assessment - E.I. Canay; M. Carante; A. Casali; E. Bernardini; D. Dondi; Dhanalakshmi Vadivel; L. Cansolino; E. Delgrosso; C. Ferrari; M. Pullia; F. Bonforte; J. Riback; et al. (Life Sciences in Space Research, 2026)

An SDS-PAGE reverse-phase metaproteomics approach for polar desert and ornithogenic soils - Kristopher Abdullah; Arkadiusz Nawrocki; Daniel Wilkins; Ling Zhong; Dana Z. Tribbia; Martin R. Larsen; Belinda C. Ferrari (Applied Soil Ecology, 2026)

Beyond phosphorus: five years of evidence for nitrate-limited cyanobacterial blooms in a large subtropical river - C. Bueno; N. Muñoz; K. Bombi-Haedo; L. Marín; A. Cabral; G. Ferrari (Hydrobiologia, 2026)

Association of meeting the 24-hour movement guidelines with heart rate variability in adults - Bruna T. C. Saraiva; William R. Tebar; Debora T. Furuta; Stefany C. B. Silva; Ewerton P. Antunes; Guilherme Sousa; Gerson Ferrari; Luiz Carlos M. Vanderlei; Diego Giulliano Destro Christofaro (European Journal of Applied Physiology, 2026)

Scaling what works: a collaborative capacity-building program tailored to optimize resources and scale evidence-based interventions for cancer prevention and control - Mary Wangen; Jingle Xu; Amy Tran; Elizabeth A. Rohan; Prajakta Adsul; Cam Escoffery; Renée M. Ferrari; Nikki Hayes; Cari Herington; Katie Jones; Jaron Hoani King; Julie Kranick; et al. (Cancer Causes & Control, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Development of biochar-immobilized Bacillus subtilis BEIB-18 for hexavalent chromium (Cr(VI)) bioremediation in aqueous medium - V. A. Schommer; M. T. Nazari; A. P. Vanin; D. D. C. Krein; N. Melo; L. F. dos Santos; G. L. Dotto; V. Ferrari; L. M. Colla; A. Dettmer; J. S. Piccin (International Journal of Environmental Science and Technology, 2026)

Measurement of the 244Cm neutron capture cross section at the n_TOF facility at CERN - V. Alcayne; A. Kimura; E. Mendoza; D. Cano-Ott; O. Aberle; F. Álvarez-Velarde; S. Amaducci; J. Andrzejewski; L. Audouin; V. Babiano-Suarez; M. Bacak; M. Barbagallo; et al. (Annals of Nuclear Energy, 2026)

Assessment of wildfire-induced hydrological changes in the south andes mountains of chile - G. Alejandra Stehr; V. Nicole Vyhmeister; C. Efraín Duarte; Francisco Nájera-De Ferrari; Vicente Saenger; Felipe Aburto; Rafael Rubilar; Carolina Merino-Guzmán; B. Francisco Matus (Journal of Hydrology, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Sustainable digitalisation - a system thinking approach for determining costs and benefits in the agri-sector - K. Soma; G. Brunori; C. Giagnocavo; F. Meulman; M. Ryan; R.M. Heredia Hortigüela; C. Iliopoulos; M. Paulus; A. Ferrari; E. Kilis; S. Grando; V. Bellon-Maurel; et al. (Agricultural Systems, 2026)

Impact of environmental gradients on juvenile coral demography across the Great Barrier Reef and Torres Strait - Christopher Doropoulos; Mariana Alvarez-Noriega; Katharina Fabricius; Renata Ferrari; Peter J. Mumby; Sam H. C. Noonan; Melanie Orr; Kinam Salee (Coral Reefs, 2025)
Demographic rates of juvenile corals are critical to reef recovery, yet their variation across environmental gradients remains understudied. Over three years, we assessed juvenile coral vital rates across the Great Barrier Reef (GBR) and Torres Strait (TS), spanning 14° latitude and diverse inshore to offshore environments. Environmental conditions varied, with annual temperatures ranging 24–28 °C, high turbidity in the southern inshore GBR, and elevated chlorophyll a in the southern offshore GBR. Despite these differences, juvenile assemblages of five common coral groups ( Montipora , Acropora , Pocilloporidae, Merulinidae, and Porites ) were broadly similar. Recruitment patterns varied with Acropora highest in southern offshore and central reefs, and Porites in southern offshore and northern reefs. Annual mortality rates were consistent across locations, but taxa-specific negative responses to turf height and sedimentation were observed. Net juvenile density increased by 3 m⁻ 2 yr⁻ 1 , with higher gains for Acropora in southern offshore reefs (3.8 m⁻ 2 yr⁻ 1 ) and Porites in northern offshore reefs (3.5 m⁻ 2 yr⁻ 1 ). Individual survival improved with size, and temperature effects were taxon-dependent—negative for Acropora , neutral for Montipora and Pocilloporidae, and positive for Merulinidae and Porites . Temperature did not correlate with linear growth in any group, but water flow positively influenced growth in most taxa. Fast-growing Acropora and Pocilloporidae showed positive size–growth relationships, unlike slower-growing Merulinidae and Porites . These findings provide baseline demographic data across the GBR and TS, revealing both congruence and divergence with ecological theory. They offer essential input for predictive models, site-specific restoration planning, and evaluating interventions relative to natural background dynamics.

Dinner or dismay? Altered behavioural response of crayfish to alarm cues when fed a conspecific diet - Gabrielle H. Achtymichuk; Kaitlyn M. Fish; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2025)

Platelet-derived growth factor receptor beta expression in primary and metastatic canine anal sac adenocarcinoma as a potential therapeutic target - A. Verdi; S. Dell'Aere; C. Zamboni; D. Stefanello; R. Ferrari; E. Gariboldi; L. Maniscalco; S. Iussich; C. Romanello; V. Grieco; C. Giudice; C. Recordati; et al. (Journal of Comparative Pathology, 2025)

Enhanced biodegradation of polylactic acid by Aspergillus oryzae lipase: Toward sustainable plastic end-of-life solutions - Christina N. Economou; Sine Mandrup Bertozzi; Martina Nardi; Uttam C. Paul; Fabrizio Fiorentini; Giorgia Ferrari; Marco Contardi; Andrea Armirotti; Despina Fragouli; Athanassia Athanassiou (Bioresource Technology, 2025)

P18-57 Assessing cardiotoxicity of compounds in a 3D Heart-on-Chip platform by evaluating alterations in cardiac electrophysiology and contractility - C. Pernici; M. Mondini; M. Rasponi; E. Ferrari; R. Visone; P. Occhetta (Toxicology Letters, 2025)

Short-term personal exposure to multiple air pollutants affects nasal microbiota in school-age children - L. Boniardi; G. Solazzo; C. Favero; L. Campo; L. Ferrari; S. Fustinoni (Science of The Total Environment, 2025)

Alternative natural supports for the immobilization of Monascus ruber: Reuse of cells and production of biopigments in submerged fermentation - Gabriel Leda Arruda; Gabriel Ferrari Paiva; Layde Teixeira Carvalho; Silvio S. da Silva; Júlio C. Santos (Journal of Environmental Chemical Engineering, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Mapping the surface properties of the Asal-Ghoubbet rift by massive inversion of the Hapke model on Pleiades multiangular images - D.T. Nguyen; S. Jacquemoud; A. Lucas; S. Douté; C. Ferrari; S. Coustance; S. Marcq; A. Meygret (Remote Sensing of Environment, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Spindle cell rhabdomyosarcoma in a cockatiel (Nymphicus hollandicus) - Tainah P. Dal Pont; Igor R. Santos; Vanessa C. Pereira; Flávia E. Ferrari; Victória R.Q. Schmidt; Marcele B. Bandinelli; Marcelo Meller Alievi; Saulo P. Pavarini (Journal of Comparative Pathology, 2025)

Wastewater based measures of COVID-19 and associations with children's absenteeism at grade schools - Helena M. Solo-Gabriele; Gabriela Guevara; Naresh Kumar; Ayaaz Amirali; Kristina M. Babler; Cynthia C. Beaver; Samuel Comerford; Maria Ferraris; Natasha Schaefer Solle; Mark E. Sharkey; Lisa Gwynn (Science of The Total Environment, 2025)

Fine-scale landscape heterogeneity drives microbial community structure at Robinson Ridge, East Antarctica - Sin Yin Wong; Nathali M. Machado-de-Lima; Daniel Wilkins; Eden Zhang; Belinda C. Ferrari (Science of The Total Environment, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Spatial Variation in Upper Limits of Coral Cover on the Great Barrier Reef - Mariana Álvarez‐Noriega; Juan C. Ortiz; Daniela M. Ceccarelli; Michael J. Emslie; Katharina E. Fabricius; Michelle J. Jonker; Marji Puotinen; Barbara J. Robson; Chris M. Roelfsema; Tane H. Sinclair‐Taylor; Renata Ferrari (Global Ecology and Biogeography, 2024)
Aim Identifying the maximum coral cover that a coral community can sustain (i.e., its ‘upper limit’) is important for predicting community dynamics and improving management strategies. Here, we quantify the relationship between estimated upper limits and key environmental factors on coral reefs: hard substrate availability, temperature and water clarity. Location Great Barrier Reef (GBR), Australia (over 1400 km). Time Period 1990 to 2022. Major Taxa Studied Scleractinian corals. Methods We used 32 years of data on coral cover around reef perimeters. Each reef was divided into four wave‐exposure habitats depending on prevailing wind conditions. For each site, we determined if hard coral cover had reached a plateau or upper limit. Next, we extracted existing estimates of hard substrate availability, modelled water temperature and Secchi depth. Then, we quantified the relationship between these environmental variables and the upper limits. Results We found varying upper limits across the GBR, with a median of 33% coral cover and only 17% of the estimated upper limits exceeded 50% coral cover. Upper limits increased towards the southern reefs. Our results show that upper limits increased with increasing hard substrate availability and decreased with temperature and, to a lesser extent, with water clarity. Main Conclusions The upper limits estimated in this study are much lower than what is commonly assumed when modelling ecological dynamics, most likely resulting in predicted recovery rates being inappropriately high. Although hard substrate ultimately restricted upper limits, there are mechanisms constraining the proportion of hard substrate that is covered by hard corals. The negative relationship between temperature and upper limits cannot be explained by changes in macroalgal abundance but may be related to changes in species composition. The quantitative relationships between the upper limits of coral cover and environmental variables will provide critical information to prioritise sites for management interventions.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Increasing road cover in urban areas is associated with greater midgut histological damage in a primitively eusocial bee - A. Ferrari; C. Polidori; C. F. Trisoglio; F. Bonasoro (Insectes Sociaux, 2024)
Urbanisation is associated with air and soil pollution, particularly from heavy metals. One of the tissues most exposed to such pollutants is the midgut epithelium as insects may ingest these pollutants with food. Bees are one of the most important urban insects, providing important ecosystem services such as pollination. However, to the best of our knowledge, no studies have investigated the possible histological alterations to the midgut epithelium of bees caused by urbanisation. We sampled workers of the ground-nesting, primitively eusocial bee Halictus scabiosae in a large metropolis (Milan), with the aim to test if individuals from areas characterised by higher urbanisation and consequently higher pollution levels—defined here by a greater proportion of roads—exhibit greater histological tissue and cellular alterations in the midgut epithelium. We obtained semi-thin sections of the midgut through histological techniques, and then adopted a semi-quantitative approach to assess morphological damage. The midgut presented a range of histological alterations including epithelium disorganisation, vacuolisation, and nucleus karyorrhexis (one of the stages of cellular death). We found higher histological damage score (calculated taking into account all found alterations) and frequency of karyorrhectic nuclei in sites with a higher proportion of roads (i.e. more urbanised). The observed alterations may underline a potential impairment of the digestive function in highly urbanised areas.

Heterosis on morphological, reproductive and productive behavior of Acroceras macrum Stapf hybrids - S. C. Ferrari Usandizaga; E. A. Brugnoli; C. E. Maidana; E. J. Martínez; C. A. Acuña (Euphytica, 2024)

LGBTQ+ cancer: priority or lip service? A qualitative content analysis of LGBTQ+ considerations in U.S. state, jurisdiction, and tribal comprehensive cancer control plans - Austin R. Waters; Madeline H. Bono; Mayuko Ito Fukunaga; Manal Masud; Megan A. Mullins; Ryan Suk; Meghan C. O’Leary; Swann A. Adams; Renée M. Ferrari; Mary Wangen; Olufeyisayo O. Odebunmi; Sarah H. Nash; et al. (Cancer Causes & Control, 2024)

Effects of increasing soil moisture on Antarctic desert microbial ecosystems - Eden Zhang; Sin Yin Wong; Paul Czechowski; Aleks Terauds; Angelique E. Ray; Nicole Benaud; Devan S. Chelliah; Daniel Wilkins; Kate Montgomery; Belinda C. Ferrari (Conservation Biology, 2024)
Overgeneralization and a lack of baseline data for microorganisms in high‐latitude environments have restricted the understanding of the microbial response to climate change, which is needed to establish Antarctic conservation frameworks. To bridge this gap, we examined over 17,000 sequence variants of bacteria and microeukarya across the hyperarid Vestfold Hills and Windmill Islands regions of eastern Antarctica. Using an extended gradient forest model, we quantified multispecies response to variations along 79 edaphic gradients to explore the effects of change and wind‐driven dispersal on community dynamics under projected warming trends. We also analyzed a second set of soil community data from the Windmill Islands to test our predictions of major environmental tipping points. Soil moisture was the most robust predictor for shaping the regional soil microbiome; the highest rates of compositional turnover occurred at 10–12% soil moisture threshold for photoautotrophs, such as Cyanobacteria , Chlorophyta , and Ochrophyta . Dust profiles revealed a high dispersal propensity for Chlamydomonas , a microalga, and higher biomass was detected at trafficked research stations. This could signal the potential for algal blooms and increased nonendemic species dispersal as human activities increase in the region. Predicted increases in moisture availability on the Windmill Islands were accompanied by high photoautotroph abundances. Abundances of rare oligotrophic taxa, such as Eremiobacterota and Candidatus Dormibacterota, which play a crucial role in atmospheric chemosynthesis, declined over time. That photosynthetic taxa increased as soil moisture increased under a warming scenario suggests the potential for competition between primary production strategies and thus a more biotically driven ecosystem should the climate become milder. Better understanding of environmental triggers will aid conservation efforts, and it is crucial that long‐term monitoring of our study sites be established for the protection of Antarctic desert ecosystems. Furthermore, the successful implementation of an improved gradient forest model presents an exciting opportunity to broaden its use on microbial systems globally.

Enteric associated T-cell lymphoma in a mule - Giovanna G. de Souza; Zara A. Lacerda; Fernanda B.C. de Moura; Isabeli J. Contel; Shéron L. de Oliveira; Lorena C. Ferrari; Emanuel V.P. Apolonio; Juliana de M. Alonso; Ana Liz G. Alves; Noeme S. Rocha (Journal of Equine Veterinary Science, 2024)

Comparison of cytologicAL and histologicAL classification systems for the detection of nodal metastases of canine mast cell tumours - A. Renzi; M.G. Ferrari; R. Zaccone; L. Marconato; C. Agnoli; S. Zanardi; S. Sabattini (Journal of Comparative Pathology, 2024)

Initial Trajectory Assessment of a low-thrust option for the RAMSES Mission to (99942) Apophis - Andrea C. Morelli; Alessandra Mannocchi; Carmine Giordano; Fabio Ferrari; Francesco Topputo (Advances in Space Research, 2024)

Performance of spray nozzles and droplet size on glufosinate deposition and weed biological efficacy - Evandro P. Prado; Júlio C. Guerreiro; Pedro J. Ferreira-Filho; Vagner do Nascimento; Samuel Ferrari; Fernando S. Galindo; Marina Funichello; Carlos G. Raetano; Paulo H. Pagliari; Rodolfo G. Chechetto; Arthur D. Rodrigues Neto (Crop Protection, 2024)

Metagenomics untangles potential adaptations of Antarctic endolithic bacteria at the fringe of habitability - Claudia Coleine; Davide Albanese; Angelique E. Ray; Manuel Delgado-Baquerizo; Jason E. Stajich; Timothy J. Williams; Stefano Larsen; Susannah Tringe; Christa Pennacchio; Belinda C. Ferrari; Claudio Donati; Laura Selbmann (Science of The Total Environment, 2024)

A Global Systematic Literature Review of Ecosystem Services in Reef Environments - Vinicius J. Giglio; Anaide W. Aued; Cesar A. M. M. Cordeiro; Linda Eggertsen; Débora S. Ferrari; Leandra R. Gonçalves; Natalia Hanazaki; Osmar J. Luiz; André L. Luza; Thiago C. Mendes; Hudson T. Pinheiro; Bárbara Segal; et al. (Environmental Management, 2024)

Droplet size and hydraulic spray nozzles in peanut plant spray deposition - Gabriela G. P. Buosi; Arthur D. R. Neto; Paulo R. M. Lopes; Samuel Ferrari; Júlio C. Guerreiro; Pedro J. F. Filho; Ronaldo C. Lima; Vagner Nascimento; Marina Funichello; Carlos G. Raetano; Evandro P. Prado (Journal of Plant Diseases and Protection, 2024)

WRF data assimilation of weather stations and lightning data for a convective event in northern Italy - E. C. Maggioni; T. Manzoni; A. Perotto; F. Spada; A. Borroni; M. Giurato; M. Giudici; F. Ferrari; D. Zardi; R. Salerno (Bulletin of Atmospheric Science and Technology, 2023)

Ethanol Production from Eucalyptus Sawdust Following Sequential Alkaline Thermochemical Pretreatment with Recovery of Extractives - M. Guigou; S. Moure; F. Bermúdez; L. Clavijo; M. N. Cabrera; L. Xavier; M. D. Ferrari; C. Lareo (BioEnergy Research, 2023)

A multidisciplinary approach to estimating wolf population size for long‐term conservation - Francesca Marucco; Maria V. Boiani; Pierre Dupont; Cyril Milleret; Elisa Avanzinelli; Kristine Pilgrim; Michael K. Schwartz; Achaz von Hardenberg; Domenica Serena Perrone; Olivier P. Friard; Arianna Menzano; Francesco Bisi; et al. (Conservation Biology, 2023)
The wolf ( Canis lupus ) is among the most controversial of wildlife species. Abundance estimates are required to inform public debate and policy decisions, but obtaining them at biologically relevant scales is challenging. We developed a system for comprehensive population estimation across the Italian alpine region (100,000 km 2 ), involving 1513 trained operators representing 160 institutions. This extensive network allowed for coordinated genetic sample collection and landscape‐level spatial capture–recapture analyses that transcended administrative boundaries to produce the first estimates of key parameters for wolf population status assessment. Wolf abundance was estimated at 952 individuals (95% credible interval 816–1120) and 135 reproductive units (i.e., packs) (95% credible interval 112–165). We also estimated that mature individuals accounted for 33–45% of the entire population. The monitoring effort was spatially estimated thereby overcoming an important limitation of citizen science data. This is an important approach for promoting wolf–human coexistence based on wolf abundance monitoring and an endorsement of large‐scale harmonized conservation practices.

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Survivin immunohistochemical expression in canine perivascular wall tumours: preliminary assessment - F. Godizzi; F. Armando; A. Cappelleri; P. Boracchi; D. Stefanello; R. Ferrari; L.E. Chiti; A. Corradi; G. Avallone; C. Pigoli; P. Roccabianca (Journal of Comparative Pathology, 2023)

Non-toxic acid-free glyoxal fixative for veterinary histopathology, immunohistochemistry and molecular analysis - V. Zappulli; F. Torrigiani; P. Detillo; S. Iussich; M. Rondena; C. Gola; L. MInoli; E. Morello; E.I. Ferraris; A. Rigillo; B. Bussolati (Journal of Comparative Pathology, 2023)

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

TimeFISH : Long‐term assessment of reef fish assemblages in a transition zone in the Southwestern Atlantic - Juan P. Quimbayo; Lucas T. Nunes; Fernanda C. Silva; Antônio B. Anderson; Diego R. Barneche; Angela M. Canterle; Isadora Cord; Andrea Dalben; Débora S. Ferrari; Luisa Fontoura; Thiago M. J. Fiuza; Ana M. R. Liedke; et al. (Ecology, 2023)
The TimeFISH database provides the first public time‐series dataset on reef fish assemblages in the southwestern Atlantic (SWA), comprising 15 years of data (2007–2022) based on standardized Underwater Visual Censuses (UVCs). The rocky reefs covered by our dataset are influenced by pronounced seasonal cycles of ocean temperatures with warm tropical waters from the Brazil Current in the summer (~27°C) and colder waters from the La Plata River Plume discharge and upwelling from the South Atlantic Central Water in the winter (~18°C). These oceanographic conditions characterize this area as the southernmost tropical–subtropical climatic transition zone in the Atlantic Ocean. As a result, reef fish assemblages are comprised of both tropical and subtropical species. All records included in TimeFISH were collected using UVCs, a nondestructive method that allows the estimation of fish species richness, abundance, and body size distributions. UVCs were performed through 40 m 2 belt transects by scuba diving in nine locations along the southern Brazilian coast (25–29°S). Four of these locations lie within the boundaries of the no‐entry Arvoredo Marine Biological Reserve, where fishing and recreational activities are forbidden, and the remaining locations are unprotected from these activities. During each belt transect, a diver swam at a constant depth above and parallel to the reef, identifying fish species, counting the number of individuals, and estimating the total body length (Lt in cm) of all detected individuals. All fish individuals in the water column (up to 2 m above the substratum) and at the bottom were targeted. In total, 202,965 individuals belonging to 163 reef fish species and 53 families were recorded across 1857 UVCs. All survey campaigns were funded by either public or mixed capital (private–public) sources, including seven grants from the Brazilian federal and Santa Catarina state governments. Part of the data has already been used in multiple MS.c. and Ph.D. theses and scientific articles. TimeFISH represents an important contribution for future studies aiming to examine temporal and spatial variations of reef fish assemblages in transition zones. No copyright restrictions apply to the use of this data set, other than citing this publication.

Textile microfibers in wild Antarctic whelk Neobuccinum eatoni (Smith, 1875) from Terra Nova Bay (Ross Sea, Antarctica) - E. Bergami; E. Ferrari; M.G.J. Löder; G. Birarda; C. Laforsch; L. Vaccari; I. Corsi (Environmental Research, 2023)

An Interlaboratory Study to Identify Potential Visible Protein-Like Particle Standards - Srivalli N. Telikepalli; Michael J. Carrier; Dean C. Ripple; Greg Barnett; Ashwinkumar Bhirde; Donna Bolton; George M. Bou-Assaf; Erica Ferrari; Scott Leigh; Sophia Levitskaya-Seaman; Tim Menzen; Felix Nikels; et al. (AAPS PharmSciTech, 2022)
Visible protein-like particle standards may improve visual inspection and/or appearance testing practices used in the biotechnology industry. They may improve assay performance resulting in better alignment and more standardized training among different companies. The National Institute of Standards and Technology (NIST) has conducted an interlaboratory study to test whether the standards under development mimic typical proteinaceous particles found in biotherapeutics and if they can be implemented during the visual inspection process. Fourteen organizations from industry and government have participated. A total of 20 labs from these 14 organizations participated with analysts from 6 formulation, 7 analytical, 4 quality control, and 3 manufacturing labs. The circulated samples consisted of abraded ethylene tetrafluoroethylene (ETFE) particles or photolithographic particles. The results consist of qualitative ratings, which varied substantially among organizations and within labs. Polydisperse ETFE particle suspensions, containing particles enriched in greater than 150 µm in size, were rated more favorably than the photolithographic particles by formulation and analytical scientists. The largest monodisperse photolithographic particles (approximately 300 µm in size) were favored equally compared to ETFE by all scientists. Solution modifications to decrease the settling rate or to alter optical properties of the ETFE solutions yielded lower ratings by the analysts. Both particle types received mixed ratings for their usability and for their application for visual inspection and for training purposes. Industry feedback will assist NIST in developing reference material(s) for visible protein-like particles. Graphical Abstract

Predator-induced transgenerational plasticity in animals: a meta-analysis - Kirsty J. MacLeod; Chloé Monestier; Maud C. O. Ferrari; Katie E. McGhee; Michael J. Sheriff; Alison M. Bell (Oecologia, 2022)
There is growing evidence that the environment experienced by one generation can influence phenotypes in the next generation via transgenerational plasticity (TGP). One of the best-studied examples of TGP in animals is predator-induced transgenerational plasticity, whereby exposing parents to predation risk triggers changes in offspring phenotypes. Yet, there is a lack of general consensus synthesizing the predator–prey literature with existing theory pertaining to ecology and evolution of TGP. Here, we apply a meta-analysis to the sizable literature on predator-induced TGP (441 effect sizes from 29 species and 49 studies) to explore five hypotheses about the magnitude, form and direction of predator-induced TGP. Hypothesis #1: the strength of predator-induced TGP should vary with the number of predator cues. Hypothesis #2: the strength of predator-induced TGP should vary with reproductive mode. Hypothesis #3: the strength and direction of predator-induced TGP should vary among offspring phenotypic traits because some traits are more plastic than others. Hypothesis #4: the strength of predator-induced TGP should wane over ontogeny. Hypothesis #5: predator-induced TGP should generate adaptive phenotypes that should be more evident when offspring are themselves exposed to risk. We found strong evidence for predator-induced TGP overall, but no evidence that parental predator exposure causes offspring traits to change in a particular direction. Additionally, we found little evidence in support of any of the specific hypotheses. We infer that the failure to find consistent evidence reflects the heterogeneous nature of the phenomena, and the highly diverse experimental designs used to study it. Together, these findings set an agenda for future work in this area.

Persistence and resistance: survival mechanisms of Candidatus Dormibacterota from nutrient‐poor Antarctic soils - Kate Montgomery; Timothy J. Williams; Merryn Brettle; Jonathan F. Berengut; Eden Zhang; Julian Zaugg; Philip Hugenholtz; Belinda C. Ferrari (Environmental Microbiology, 2022)

BAG2 prevents Tau hyperphosphorylation and increases p62/SQSTM1 in cell models of neurodegeneration - Raquel S. Lima; Daniel C. Carrettiero; Merari F. R. Ferrari (Molecular Biology Reports, 2022)

Soil substrate culturing approaches recover diverse members of Actinomycetota from desert soils of Herring Island, East Antarctica - Nicole Benaud; Devan S. Chelliah; Sin Yin Wong; Belinda C. Ferrari (Extremophiles, 2022)
Antimicrobial resistance is an escalating health crisis requiring urgent action. Most antimicrobials are natural products (NPs) sourced from Actinomycetota , particularly the Streptomyces . Underexplored and extreme environments are predicted to harbour novel microorganisms with the capacity to synthesise unique metabolites. Herring Island is a barren and rocky cold desert in East Antarctica, remote from anthropogenic impact. We aimed to recover rare and cold-adapted NP-producing bacteria, by employing two culturing methods which mimic the natural environment: direct soil culturing and the soil substrate membrane system. First, we analysed 16S rRNA gene amplicon sequencing data from 18 Herring Island soils and selected the soil sample with the highest Actinomycetota relative abundance (78%) for culturing experiments. We isolated 166 strains across three phyla, including novel and rare strains, with 94% of strains belonging to the Actinomycetota . These strains encompassed thirty-five ‘species’ groups, 18 of which were composed of Streptomyces strains. We screened representative strains for genes which encode polyketide synthases and non-ribosomal peptide synthetases, indicating that 69% have the capacity to synthesise polyketide and non-ribosomal peptide NPs. Fourteen Streptomyces strains displayed antimicrobial activity against selected bacterial and yeast pathogens using an in situ assay. Our results confirm that the cold-adapted bacteria of the harsh East Antarctic deserts are worthy targets in the search for bioactive compounds.

Long-term use of pharmacological treatment in Alzheimer’s disease: a retrospective cohort study in real-world clinical practice - G Lombardi; N Lombardi; A Bettiol; G Crescioli; C Ferrari; G Lucidi; C Polito; V Berti; V Bessi; S Bagnoli; B Nacmias; A Vannacci; et al. (European Journal of Clinical Pharmacology, 2022)

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

Effects of Magnetite Nanoparticles and Static Magnetic Field on Neural Differentiation of Pluripotent Stem Cells - Ana T. Semeano; Fabiano A. Tofoli; Juliana C. Corrêa-Velloso; Ana P. de Jesus Santos; Ágatha Oliveira-Giacomelli; Rafaela R. Cardoso; Mateus A. Pessoa; Edroaldo Lummertz da Rocha; Gustavo Ribeiro; Merari F. R. Ferrari; Lygia V. Pereira; Yang D. Teng; et al. (Stem Cell Reviews and Reports, 2022)

Effects of application rate on spray deposition, stink bug control, and yield in soybean crops - José L. C. Santos-Júnior; Carlos G. Raetano; Fernando K. de Carvalho; Pedro J. Ferreira-Filho; Júlio C. Guerreiro; Samuel Ferrari; Vagner Nascimento; Rafael S. Tomaz; Agatha S. Argioli; Evandro P. Prado (Phytoparasitica, 2022)

Sensitivity Analysis of Single Beat Left Ventricular Elastance Estimation by Chen Method - A. Di Molfetta; G. Ferrari; V. Cusimano; G. Di Ruzza; P. Mollo; D. Boncompagni; M. Cesario; C. Volponi; M. Massetti; M. Menichelli (Cardiovascular Engineering and Technology, 2022)

Disturbance cues facilitate associative learning of predators in a coral reef fish - Michael S. Pollock; Zoe Hoyle; Mark I. Mccormick; Douglas P. Chivers; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2021)

Exposure to degraded coral habitat depresses oxygen uptake rate during exercise of a juvenile reef fish - Adam T. Downie; Caroline M. Phelps; Rhondda Jones; Jodie L. Rummer; Douglas P. Chivers; Maud C. O. Ferrari; Mark I. McCormick (Coral Reefs, 2021)

Persistence and resistance: survival mechanisms of Candidatus Dormibacterota from nutrient‐poor Antarctic soils - Kate Montgomery; Timothy J. Williams; Merryn Brettle; Jonathan F. Berengut; Angelique E. Ray; Eden Zhang; Julian Zaugg; Philip Hugenholtz; Belinda C. Ferrari (Environmental Microbiology, 2021)
Summary Candidatus Dormibacterota is an uncultured bacterial phylum found predominantly in soil that is present in high abundances within cold desert soils. Here, we interrogate nine metagenome‐assembled genomes ( MAGs ), including six new MAGs derived from soil metagenomes obtained from two eastern Antarctic sites. Phylogenomic and taxonomic analyses revealed these MAGs represent four genera and five species, representing two order‐level clades within Ca . Dormibacterota. Metabolic reconstructions of these MAGs revealed the potential for aerobic metabolism, and versatile adaptations enabling persistence in the ‘extreme’ Antarctic environment. Primary amongst these adaptations were abilities to scavenge atmospheric H 2 and CO as energy sources, as well as using the energy derived from H 2 oxidation to fix atmospheric CO 2 via the Calvin–Bassham–Benson cycle, using a RuBisCO type IE . We propose that these allow Ca . Dormibacterota to persist using H 2 oxidation and grow using atmospheric chemosynthesis in terrestrial Antarctica. Fluorescence in situ hybridization revealed Ca . Dormibacterota to be coccoid cells, 0.3–1.4 μm in diameter, with some cells exhibiting the potential for a symbiotic or syntrophic lifestyle.

New Horizons on Non-invasive Brain Stimulation of the Social and Affective Cerebellum - Z. Cattaneo; C. Ferrari; A. Ciricugno; E. Heleven; D. J. L. G. Schutter; M. Manto; F. Van Overwalle (The Cerebellum, 2021)

Antarctic desert soil bacteria exhibit high novel natural product potential, evaluated through long‐read genome sequencing and comparative genomics - Nicole Benaud; Richard J. Edwards; Timothy G. Amos; Paul M. D'Agostino; Carolina Gutiérrez‐Chávez; Kate Montgomery; Iskra Nicetic; Belinda C. Ferrari (Environmental Microbiology, 2021)
Summary Actinobacteria and Proteobacteria are important producers of bioactive natural products (NP), and these phyla dominate in the arid soils of Antarctica, where metabolic adaptations influence survival under harsh conditions. Biosynthetic gene clusters (BGCs) which encode NPs, are typically long and repetitious high G + C regions difficult to sequence with short‐read technologies. We sequenced 17 Antarctic soil bacteria from multi‐genome libraries, employing the long‐read PacBio platform, to optimize capture of BGCs and to facilitate a comprehensive analysis of their NP capacity. We report 13 complete bacterial genomes of high quality and contiguity, representing 10 different cold‐adapted genera including novel species. Antarctic BGCs exhibited low similarity to known compound BGCs (av. 31%), with an abundance of terpene, non‐ribosomal peptide and polyketide‐encoding clusters. Comparative genome analysis was used to map BGC variation between closely related strains from geographically distant environments. Results showed the greatest biosynthetic differences to be in a psychrotolerant Streptomyces strain, as well as a rare Actinobacteria genus, Kribbella , while two other Streptomyces spp. were surprisingly similar to known genomes. Streptomyces and Kribbella BGCs were predicted to encode antitumour, antifungal, antibacterial and biosurfactant‐like compounds, and the synthesis of NPs with antibacterial, antifungal and surfactant properties was confirmed through bioactivity assays.

Consensus Paper: Cerebellum and Social Cognition - Frank Van Overwalle; Mario Manto; Zaira Cattaneo; Silvia Clausi; Chiara Ferrari; John D. E. Gabrieli; Xavier Guell; Elien Heleven; Michela Lupo; Qianying Ma; Marco Michelutti; Giusy Olivito; et al. (The Cerebellum, 2020)
The traditional view on the cerebellum is that it controls motor behavior. Although recent work has revealed that the cerebellum supports also nonmotor functions such as cognition and affect, only during the last 5 years it has become evident that the cerebellum also plays an important social role. This role is evident in social cognition based on interpreting goal-directed actions through the movements of individuals (social “mirroring”) which is very close to its original role in motor learning, as well as in social understanding of other individuals’ mental state, such as their intentions, beliefs, past behaviors, future aspirations, and personality traits (social “mentalizing”). Most of this mentalizing role is supported by the posterior cerebellum (e.g., Crus I and II). The most dominant hypothesis is that the cerebellum assists in learning and understanding social action sequences, and so facilitates social cognition by supporting optimal predictions about imminent or future social interaction and cooperation. This consensus paper brings together experts from different fields to discuss recent efforts in understanding the role of the cerebellum in social cognition, and the understanding of social behaviors and mental states by others, its effect on clinical impairments such as cerebellar ataxia and autism spectrum disorder, and how the cerebellum can become a potential target for noninvasive brain stimulation as a therapeutic intervention. We report on the most recent empirical findings and techniques for understanding and manipulating cerebellar circuits in humans. Cerebellar circuitry appears now as a key structure to elucidate social interactions.

IL-33 enhances macrophage release of IL-1β and promotes pain and inflammation in gouty arthritis - Victor Fattori; Larissa Staurengo-Ferrari; Tiago H. Zaninelli; Rubia Casagrande; Rene D. Oliveira; Paulo Louzada-Junior; Thiago M. Cunha; Jose C. Alves-Filho; Mauro M. Teixeira; Fernando Q. Cunha; Flavio A. Amaral; Waldiceu A. Verri (Inflammation Research, 2020)

Forget the audience: tadpoles release similar disturbance cues regardless of kinship or familiarity - Kevin R. Bairos-Novak; Adam L. Crane; Gabrielle H. Achtymichuk; Jonathan Hsin; Ita A. E. Rivera-Hernández; Olena M. Simko; Theresa E. Wrynn; Douglas P. Chivers; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Seismological analyses of the seismic microzonation of 138 municipalities damaged by the 2016–2017 seismic sequence in Central Italy - E. Priolo; F. Pacor; D. Spallarossa; G. Milana; G. Laurenzano; M. A. Romano; C. Felicetta; S. Hailemikael; F. Cara; G. Di Giulio; G. Ferretti; C. Barnaba; et al. (Bulletin of Earthquake Engineering, 2020)
This paper describes the seismological analyses performed within the framework of the seismic microzonation study for the reconstruction of 138 municipalities damaged by the 2016–2017 sequence in Central Italy. Many waveforms were recorded over approximately 15 years at approximately 180 instrumented sites equipped with permanent or temporary stations in an area that includes all the damaged localities. Site response was assessed using earthquake and noise recordings at the selected stations through different parameters, such as spectral amplification curves, fundamental resonance frequencies, site-specific response spectra, and average amplification factors. The present study was a collaboration of many different institutions under the coordination of the Italian Center for Seismic Microzonation and its applications . The results were homogenized and gathered into site-specific forms, which represent the main deliverable for the benefit of Italian Civil Protection. It is remarkable that the bulk of this study was performed in a very short period (approximately 2 months) to provide quantitative information for detailed microzonation and future reconstruction of the damaged municipalities.

Proportional fitness loss and the timing of defensive investment: a cohesive framework across animals and plants - Michael J. Sheriff; John L. Orrock; Maud C. O. Ferrari; Richard Karban; Evan L. Preisser; Andrew Sih; Jennifer S. Thaler (Oecologia, 2020)

Distinct assembly mechanisms underlie similar biogeographical patterns of rare and abundant bacteria in Tibetan Plateau grassland soils - Mukan Ji; Weidong Kong; James Stegen; Linyan Yue; Fei Wang; Xiaobin Dong; Don A Cowan; Belinda C Ferrari (Environmental Microbiology, 2020)
Summary Rare biosphere represents the majority of Earth's biodiversity and performs vital ecological functions, yet little is known about its biogeographical patterns and community assembly processes in terrestrial ecosystems. Herein, we investigated the community composition and phylogeny of rare (relative abundance 1%) bacteria in dryland grassland soils on the Tibetan Plateau. Results revealed similar biogeographical patterns of rare and abundant bacteria at both compositional and phylogenetic levels, but rare subcommunity was more heavily influenced by stochasticity (72%) than the abundant (57%). The compositional variation of rare bacteria was less explained by environmental factors (41%) than that of the abundant (80%), while the phylogeny of rare bacteria (36%) was more explained than that of the abundant (29%). The phylogeny of rare bacteria was equally explained by local factors (soil and vegetation) and geospatial distance (11.5% and 11.9% respectively), while that of the abundant was more explained by geospatial distance (22.1%) than local factors (11.3%). Furthermore, a substantially tighter connection between the community phylogeny and composition was observed in rare ( R 2 = 0.65) than in abundant bacteria ( R 2 = 0.08). Our study provides novel insights into the assembly processes and biographical patterns of rare and abundant bacteria in dryland soils.

Cellular and molecular effects of silymarin on the transdifferentiation processes of LX-2 cells and its connection with lipid metabolism - Caio Mateus Silva; Gustavo Duarte Ferrari; Luciane Carla Alberici; Osmar Malaspina; Karen C. M. Moraes (Molecular and Cellular Biochemistry, 2020)

Lime and gypsum combination improves crop and forage yields and estimated meat production and revenue in a variable charge tropical soil - Carlos A. C. Crusciol; Rubia R. Marques; Antonio C. A. Carmeis Filho; Rogério P. Soratto; Claudio H. M. Costa; Jayme Ferrari Neto; Gustavo S. A. Castro; Cristiano M. Pariz; André M. Castilhos; Alan J. Franzluebbers (Nutrient Cycling in Agroecosystems, 2019)

Comparative diversity of anemone-associated fishes and decapod crustaceans in a Belizean coral reef and seagrass system - Rohan M. Brooker; William E. Feeney; Tiffany L. Sih; Maud. C. O. Ferrari; Douglas P. Chivers (Marine Biodiversity, 2019)

Does Sugarcane Straw Removal Change the Abundance of Soil Microbes? - Maristela C. Morais; Beatriz M. Ferrari; Clovis D. Borges; Maurício R. Cherubin; Siu Mui Tsai; Carlos C. Cerri; Carlos E. P. Cerri; Brigitte J. Feigl (BioEnergy Research, 2019)

Refugia under threat: Mass bleaching of coral assemblages in high‐latitude eastern Australia - Sun W. Kim; Eugenia M. Sampayo; Brigitte Sommer; Carrie A. Sims; Maria del C. Gómez‐Cabrera; Steve J. Dalton; Maria Beger; Hamish A. Malcolm; Renata Ferrari; Nicola Fraser; Will F. Figueira; Stephen D. A. Smith; et al. (Global Change Biology, 2019)
Environmental anomalies that trigger adverse physiological responses and mortality are occurring with increasing frequency due to climate change. At species' range peripheries, environmental anomalies are particularly concerning because species often exist at their environmental tolerance limits and may not be able to migrate to escape unfavourable conditions. Here, we investigated the bleaching response and mortality of 14 coral genera across high‐latitude eastern Australia during a global heat stress event in 2016. We evaluated whether the severity of assemblage‐scale and genus‐level bleaching responses was associated with cumulative heat stress and/or local environmental history, including long‐term mean temperatures during the hottest month of each year (SST LTMAX ), and annual fluctuations in water temperature (SST VAR ) and solar irradiance (PARZ VAR ). The most severely‐bleached genera included species that were either endemic to the region ( Pocillopora aliciae ) or rare in the tropics (e.g. Porites heronensis ). Pocillopora spp., in particular, showed high rates of immediate mortality. Bleaching severity of Pocillopora was high where SST LTMAX was low or PARZ VAR was high, whereas bleaching severity of Porites was directly associated with cumulative heat stress. While many tropical Acropora species are extremely vulnerable to bleaching, the Acropora species common at high latitudes, such as A. glauca and A. solitaryensis , showed little incidence of bleaching and immediate mortality. Two other regionally‐abundant genera, Goniastrea and Turbinaria , were also largely unaffected by the thermal anomaly. The severity of assemblage‐scale bleaching responses was poorly explained by the environmental parameters we examined. Instead, the severity of assemblage‐scale bleaching was associated with local differences in species abundance and taxon‐specific bleaching responses. The marked taxonomic disparity in bleaching severity, coupled with high mortality of high‐latitude endemics, point to climate‐driven simplification of assemblage structures and progressive homogenisation of reef functions at these high‐latitude locations.

Evaluating adaptive, carry‐over, and plastic antipredator responses across a temporal gradient in Pacific chorus frogs - Tiffany S. Garcia; Evan M. Bredeweg; Jenny Urbina; Maud C. O. Ferrari (Ecology, 2019)
The development of antipredator traits is dependent on the frequency and intensity of predator exposure over evolutionary and ecological time. We hypothesized that prey species would respond with increasing accuracy when exposed to predators across generational, ontogenetic, and immediate time scales. We assessed larval Pacific chorus frog ( PSRE ; Pseudacris regilla ) individuals that varied in population sympatry, embryonic conditioning, and immediate exposure to stocked populations of rainbow trout ( Oncorhynchus mykiss ). Using PSRE populations from sites with and without resident rainbow trout, we conditioned embryos to trout odor, PSRE alarm cues, trout odor in combination with alarm cues, or control water. After being hatched and reared in control water, individuals were exposed to the four predator cue treatments using a fully factorial design. Tadpoles from populations with resident rainbow trout did not behave or develop differently than tadpoles originating from fishless sites. However, we found evidence that PSRE reduced predation risk with a combination of carry‐over effect (i.e., transfer of information across life history stages) and within‐life stage phenotypically plastic mechanisms. We found both developmental and behavioral carry‐over effects: tadpoles conditioned with trout odor as embryos grew more slowly and took refuge more often than control animals. Within‐life‐stage behavioral plasticity was observed in tadpoles from all treatment groups, responding to predator cues with increased refuge use. Potentially additive effects of predator exposure on prey response should be considered when predicting the ability of prey to recognize novel threats.

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Survival, behaviour, and morphology of larval wood frogs, Lithobates sylvaticus, under threat from an exotic crayfish predator, Orconectes virilis - Adam L. Crane; Kevin R. Bairos-Novak; Dale M. Jefferson; Douglas P. Chivers; Maud C. O. Ferrari (Aquatic Ecology, 2019)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Stereotactic radiation therapy in oligometastatic colorectal cancer: outcome of 102 patients and 150 lesions - V. Dell’Acqua; A. Surgo; F. Kraja; J. Kobiela; Maria Alessia Zerella; P. Spychalski; S. Gandini; C. M. Francia; D. Ciardo; C. Fodor; A. M. Ferrari; G. Piperno; et al. (Clinical & Experimental Metastasis, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

The Effects of Selenomethionine on the Escape Behaviours of Fathead Minnows - Philip J. Anderson; Matthew D. Mitchell; Katherine J. Fedoroff; Douglas P. Chivers; Maud C. O. Ferrari (Archives of Environmental Contamination and Toxicology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Diallelic Analysis of Endogamic Maize Lines with Emphasis on Agronomic Traits of Tassel in Different Environments - D. Barreta; M. Nardino; V. A. Konflanz; A. J. de Pelegrin; M. Ferrari; V. J. Szareski; I. R. Carvalho; V. Q. de Souza; A. C. de Oliveira; L. C. da Maia (Journal of Crop Science and Biotechnology, 2019)

Who’s where? Ecological uncertainty shapes neophobic predator avoidance in Trinidadian guppies - Laurence E. A. Feyten; Ebony E. E. M. Demers; Indar W. Ramnarine; Douglas P. Chivers; Maud C. O. Ferrari; Grant E. Brown (Behavioral Ecology and Sociobiology, 2019)

Interaction between the production of ethanol and glycerol in fed-batch bioreactors - Márcia Justino Rossini Mutton; Fernanda C. S. Ferrari; Lidyane Aline de Freita; Cristhyane Millena de Freita; Maria da Graça S. Andrietta; Silvio Roberto Andrietta (Brazilian Journal of Microbiology, 2019)

Chronic Hippocampal Expression of Notch Intracellular Domain Induces Vascular Thickening, Reduces Glucose Availability, and Exacerbates Spatial Memory Deficits in a Rat Model of Early Alzheimer - Pablo Galeano; María C. Leal; Carina C. Ferrari; María C. Dalmasso; Pamela V. Martino Adami; María I. Farías; Juan C. Casabona; Mariana Puntel; Sonia Do Carmo; Clara Smal; Martín Arán; Eduardo M. Castaño; et al. (Molecular Neurobiology, 2018)

The effect of type-B carbonate content on the elasticity of fluorapatite - Fernando Cámara; Nadia Curetti; Piera Benna; Yassir A. Abdu; Frank C. Hawthorne; Cristiano Ferraris (Physics and Chemistry of Minerals, 2018)

Endoscopy, histology and electron microscopy analysis of foetal membranes in pregnant South American plains vizcacha reveal unusual excrescences on the yolk sac - Mariela Giacchino; Pablo I. F. Inserra; Fernando D. Lange; María C. Gariboldi; Sergio R. Ferraris; Alfredo D. Vitullo (Journal of Molecular Histology, 2018)

Quercetin inhibits gout arthritis in mice: induction of an opioid-dependent regulation of inflammasome - Kenji W. Ruiz-Miyazawa; Larissa Staurengo-Ferrari; Sandra S. Mizokami; Talita P. Domiciano; Fabiana T. M. C. Vicentini; Doumit Camilios-Neto; Wander R. Pavanelli; Phileno Pinge-Filho; Flávio A. Amaral; Mauro M. Teixeira; Rubia Casagrande; Waldiceu A. Verri (Inflammopharmacology, 2017)

Embryonic learning and developmental carry-over effects in an invasive anuran - Tiffany S. Garcia; Jenny C. Urbina; Evan M. Bredeweg; Maud C. O. Ferrari (Oecologia, 2017)

Probucol attenuates overt pain-like behavior and carrageenan-induced inflammatory hyperalgesia and leukocyte recruitment by inhibiting NF-кB activation and cytokine production without antioxidant effects - Amanda Z. Zucoloto; Marília F. Manchope; Larrisa Staurengo-Ferrari; José C. Alves-Filho; Thiago M. Cunha; Maísa M. Antunes; Gustavo B. Menezes; Fernando Q. Cunha; Rubia Casagrande; Waldiceu A. Verri (Inflammation Research, 2017)

Cortical Spreading Depression Causes Unique Dysregulation of Inflammatory Pathways in a Transgenic Mouse Model of Migraine - Else Eising; Reinald Shyti; Peter A. C. ’t Hoen; Lisanne S. Vijfhuizen; Sjoerd M. H. Huisman; Ludo A. M. Broos; Ahmed Mahfouz; Marcel J. T. Reinders; Michel D. Ferrari; Else A. Tolner; Boukje de Vries; Arn M. J. M. van den Maagdenberg (Molecular Neurobiology, 2017)

Solar photocatalytic degradation of textile effluent with TiO2, ZnO, and Nb2O5 catalysts: assessment of photocatalytic activity and mineralization - Renata P. Souza; Elizangela Ambrosio; Maisa T. F. Souza; Thábata K. F. S. Freitas; Ana M. Ferrari-Lima; Juliana C. Garcia (Environmental Science and Pollution Research, 2017)

Perovskite-type titanate zirconate as photocatalyst for textile wastewater treatment - A. M. Ferrari-Lima; A. C. Ueda; E. A. Bergamo; R. G. Marques; E. A. V. Ferri; C. S. Pinto; C. A. A. Pereira; P. H. Yassue-Cordeiro; R. P. Souza (Environmental Science and Pollution Research, 2017)

Impairment of mitochondria dynamics by human A53T α-synuclein and rescue by NAP (davunetide) in a cell model for Parkinson’s disease - T. Q. Melo; K. C. van Zomeren; M. F. R. Ferrari; H. W. G. M. Boddeke; J. C. V. M. Copray (Experimental Brain Research, 2017)

Cystic fibrosis in Afro-Brazilians: XK haplotypes analysis supports the European origin of p.F508del mutation - D. A. S. de Souza; F. R. Faucz; R. B. de Alexandre; M. A. Santana; E. L. S. de Souza; F. J. C. Reis; L. Pereira-Ferrari; V. S. Sotomaior; L. Culpi; J. A. Phillips; S. Raskin (Genetica, 2017)

Habitat degradation disrupts neophobia in juvenile coral reef fish - Mark I. McCormick; Douglas P. Chivers; Bridie J. M. Allan; Maud C. O. Ferrari (Global Change Biology, 2017)
Habitat degradation not only disrupts habitat‐forming species, but alters the sensory landscape within which most species must balance behavioural activities against predation risk. Rapidly developing a cautious behavioural phenotype, a condition known as neophobia, is advantageous when entering a novel risky habitat. Many aquatic organisms rely on damage‐released conspecific cues (i.e. alarm cues) as an indicator of impending danger and use them to assess general risk and develop neophobia. This study tested whether settlement‐stage damselfish associated with degraded coral reef habitats were able to use alarm cues as an indicator of risk and, in turn, develop a neophobic response at the end of their larval phase. Our results indicate that fish in live coral habitats that were exposed to alarm cues developed neophobia, and, in situ , were found to be more cautious, more closely associated with their coral shelters and survived four‐times better than non‐neophobic control fish. In contrast, fish that settled onto degraded coral habitats did not exhibit neophobia and consequently suffered much greater mortality on the reef, regardless of their history of exposure to alarm cues. Our results show that habitat degradation alters the efficacy of alarm cues with phenotypic and survival consequences for newly settled recruits.

Polymorphisms of dopamine receptor genes and risk of visual hallucinations in Parkinson’s patients - M Ferrari; C Comi; F Marino; L Magistrelli; F De Marchi; R Cantello; G Riboldazzi; G Bono; M Cosentino (European Journal of Clinical Pharmacology, 2016)

Thermal environment and nutritional condition affect the efficacy of chemical alarm cues produced by prey fish - Govinda D. H. Lienart; Maud C. O. Ferrari; Mark I. McCormick (Environmental Biology of Fishes, 2016)

Multiple geographic origins and high genetic differentiation of the Alpine marmots reintroduced in the Pyrenees - Coraline Bichet; Sandrine Sauzet; Laetitia Averty; Pierre Dupont; Mariona Ferrandiz-Rovira; Caterina Ferrari; Irene Figueroa; Marion Tafani; Célia Rézouki; Bernat C. López; Aurélie Cohas (Conservation Genetics, 2016)

Diet cues alter the development of predator recognition templates in tadpoles - Matthew D. Mitchell; Maud C. O. Ferrari; Tyrone Lucon-Xiccato; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2016)

”LOVE TO HATE” pesticides: felicity or curse for the soil microbial community? An FP7 IAPP Marie Curie project aiming to establish tools for the assessment of the mechanisms controlling the interactions of pesticides with soil microorganisms - D. G. Karpouzas; G. Tsiamis; M. Trevisan; F. Ferrari; C. Malandain; O. Sibourg; F. Martin-Laurent (Environmental Science and Pollution Research, 2016)

Comparison of abdominal adiposity and overall obesity in relation to risk of small intestinal cancer in a European Prospective Cohort - Yunxia Lu; Amanda J. Cross; Neil Murphy; Heinz Freisling; Ruth C. Travis; Pietro Ferrari; Verena A. Katzke; Rudolf Kaaks; Åsa Olsson; Ingegerd Johansson; Frida Renström; Salvatore Panico; et al. (Cancer Causes & Control, 2016)

Pyrrolidine dithiocarbamate inhibits superoxide anion-induced pain and inflammation in the paw skin and spinal cord by targeting NF-κB and oxidative stress - Felipe A. Pinho-Ribeiro; Victor Fattori; Ana C. Zarpelon; Sergio M. Borghi; Larissa Staurengo-Ferrari; Thacyana T. Carvalho; Jose C. Alves-Filho; Fernando Q. Cunha; Thiago M. Cunha; Rubia Casagrande; Waldiceu A. Verri (Inflammopharmacology, 2016)

Geological connectivity drives microbial community structure and connectivity in polar, terrestrial ecosystems - Belinda C. Ferrari; Andrew Bissett; Ian Snape; Josie van Dorst; Anne S. Palmer; Mukan Ji; Steven D. Siciliano; Jonathon S. Stark; Tristrom Winsley; Mark V. Brown (Environmental Microbiology, 2016)
Summary Landscape heterogeneity impacts community assembly in animals and plants, but it is not clear if this ecological concept extends to microbes. To examine this question, we chose to investigate polar soil environments from the Antarctic and Arctic, where microbes often form the major component of biomass. We examined soil environments that ranged in connectivity from relatively well‐connected slopes to patchy, fragmented landforms that comprised isolated frost boils. We found landscape connectedness to have a significant correlation with microbial community structure and connectivity, as measured by co‐occurrence networks. Soils from within fragmented landforms appeared to exhibit less local environmental heterogeneity, harboured more similar communities, but fewer biological associations than connected landforms. This effect was observed at both poles, despite the geographical distances and ecological differences between them. We suggest that microbial communities inhabiting well‐connected landscape elements respond consistently to regional‐scale gradients in biotic and edaphic factors. Conversely, the repeated freeze thaw cycles that characterize fragmented landscapes create barriers within the landscape and act to homogenize the soil environment within individual frost boils and consequently the microbial communities. We propose that lower microbial connectivity in the fragmented landforms is a function of smaller patch size and continual disturbances following soil mixing.

Genetic introgression of hybrid Rhododendron x intermedium Tausch is habitat mediated: Evidences from south-eastern Alps (Italy) - I. Bruni; F. De Mattia; S. Fluch; C. Ferrari; M. Corazza; E. Dinelli; M. Labra (Plant Biosystems, 2016)

Microbial diversity at Mitchell Peninsula, Eastern Antarctica: a potential biodiversity “hotspot” - Mukan Ji; Josie van Dorst; Andrew Bissett; Mark V. Brown; Anne S. Palmer; Ian Snape; Steven D. Siciliano; Belinda C. Ferrari (Polar Biology, 2016)

Specific global responses to N and Fe nutrition in toxic and non‐toxic Microcystis aeruginosa - Ralitza Alexova; The Cuong Dang; Manabu Fujii; Mark J. Raftery; T. David Waite; Belinda C. Ferrari; Brett A. Neilan (Environmental Microbiology, 2016)
Summary The bloom‐forming cyanobacteria species M icrocystis aeruginosa includes toxic and non‐toxic (microcystin‐producing) strains. Certain stress conditions stimulate synthesis of microcystin ( MCYST ) and enhance the binding of the MCYST molecule to proteins. In this quantitative proteomic study, we compared the response of a wild‐type toxic strain PCC 7806, an mcyH − knockout non‐toxic strain, and a naturally occurring non‐toxic strain, PCC 7005, after 8 days in low iron ( F e) and nitrogen ( N ) starvation in order to assess the benefit of MCYST synthesis in non‐optimal conditions. Fe limitation increased MCYST synthesis and caused an accumulation of phycobilisome proteins and the ferric iron transporter FutA only in the toxic PCC 7806 but not the non‐toxic strains. In N starvation, photosynthetic, C and N metabolism proteins were more abundant in the non‐toxic strains, as were chaperones and proteases. Significant interaction between nutrient availability and toxicity existed for thioredoxin peroxidase and several thioredoxin‐regulated proteins. We propose a competition of MCYST for binding sites in thioredoxin‐regulated proteins during oxidative stress (low F e) but not in growth‐limiting conditions (low N ). This then leads to differences in the regulation of C : N metabolism in toxic and non‐toxic M . aeruginosa in nutrient‐replete and nutrient‐limited conditions.

Individual vs. social learning of predator information in fish: does group size affect learning efficacy? - Anthony G. E. Mathiron; Adam L. Crane; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2015)

Insect life history and the evolution of bacterial mutualism - Lee M. Henry; Martin C. J. Maiden; Julia Ferrari; H. Charles J. Godfray (Ecology Letters, 2015)
Bacterial symbiosis has played a fundamental role in the evolution of eukaryotes. However, we still know little about how cooperative relationships with bacteria originate, and why they form in some host species but not others. Facultative symbionts that are beneficial, but not essential, provide unique insights into these processes. We use data from over a hundred aphid species to test if host life history is associated with the presence of facultative symbionts. We find that aphid species that have mutualistic associations with ants that protect them from natural enemies are less likely to carry symbionts that provide similar benefits. We also find one symbiont species occurs more frequently in unrelated aphid species that specialise on certain plant genera. In addition, aphid species that attack multiple plants often carry different symbiont complements. Our findings provide evidence of the ecological conditions that facilitate stable, mutually beneficial relationships between microbes and eukaryotic hosts.

Background risk and recent experience influences retention of neophobic responses to predators - Grant E. Brown; Chris K. Elvidge; Indar Ramnarine; Maud C. O. Ferrari; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2015)

Interactive effects of ocean acidification and rising sea temperatures alter predation rate and predator selectivity in reef fish communities - Maud. C. O. Ferrari; Philip L. Munday; Jodie L. Rummer; Mark I. McCormick; Katherine Corkill; Sue‐Ann Watson; Bridie J. M. Allan; Mark G. Meekan; Douglas P. Chivers (Global Change Biology, 2015)
Ocean warming and acidification are serious threats to marine life. While each stressor alone has been studied in detail, their combined effects on the outcome of ecological interactions are poorly understood. We measured predation rates and predator selectivity of two closely related species of damselfish exposed to a predatory dottyback. We found temperature and CO 2 interacted synergistically on overall predation rate, but antagonistically on predator selectivity. Notably, elevated CO 2 or temperature alone reversed predator selectivity, but the interaction between the two stressors cancelled selectivity. Routine metabolic rates of the two prey showed strong species differences in tolerance to CO 2 and not temperature, but these differences did not correlate with recorded mortality. This highlights the difficulty of linking species‐level physiological tolerance to resulting ecological outcomes. This study is the first to document both synergistic and antagonistic effects of elevated CO 2 and temperature on a crucial ecological process like predator–prey dynamics.

Automatic detection of motion blur in intravital video microscopy image sequences via directional statistics of log-Gabor energy maps - Ricardo J. Ferrari; Carlos H. Villa Pinto; Bruno C. Gregório da Silva; Danielle Bernardes; Juliana Carvalho-Tavares (Medical & Biological Engineering & Computing, 2015)

Seismicity of Northwestern Italy during the last 30 years - D. Scafidi; S. Barani; R. De Ferrari; G. Ferretti; M. Pasta; M. Pavan; D. Spallarossa; C. Turino (Journal of Seismology, 2015)

Fish community structure as an indicator of the long-term effects of the damming of an Amazonian river - Júlio C. Sá-Oliveira; Victoria J. Isaac; Stephen F. Ferrari (Environmental Biology of Fishes, 2015)

Latitudinal pattern in plant composition along the Peruvian and Chilean fog oases - R. Manrique; C. Ricotta; C. Ferrari; G. Pezzi (Plant Biosystems, 2014)

Social learning of predators by coral reef fish: does observer number influence acquisition of information? - R. P. Manassa; M. I. McCormick; D. L. Dixson; M. C. O. Ferrari; D. P. Chivers (Behavioral Ecology and Sociobiology, 2014)

The Effects of Chronic Exposure to Environmentally Relevant Levels of Waterborne Cadmium on Reproductive Capacity and Behaviour in Fathead Minnows - Yinxian Wang; Maud C. O. Ferrari; Zachary Hoover; Ali M. Yousafzai; Douglas P. Chivers; Som Niyogi (Archives of Environmental Contamination and Toxicology, 2014)

Bronchial microbiome of severe COPD patients colonised by Pseudomonas aeruginosa - L. Millares; R. Ferrari; M. Gallego; M. Garcia-Nuñez; V. Pérez-Brocal; M. Espasa; X. Pomares; C. Monton; A. Moya; E. Monsó (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Dietary intake of acrylamide and esophageal cancer risk in the European Prospective Investigation into Cancer and Nutrition cohort - Leila Lujan-Barroso; Carlos Alberto González; Nadia Slimani; Mireia Obón-Santacana; Pietro Ferrari; Heinz Freisling; Kim Overvad; Françoise Clavel-Chapelon; Marie-Christine Boutron-Ruault; Antoine Racine; Verena Katzke; Tilman Kühn; et al. (Cancer Causes & Control, 2014)

Frugal cannibals: how consuming conspecific tissues can provide conditional benefits to wood frog tadpoles (Lithobates sylvaticus) - Dale M. Jefferson; Keith A. Hobson; Brandon S. Demuth; Maud C. O. Ferrari; Douglas P. Chivers (The Science of Nature, 2014)

Modeling the spread of invasive species using dynamic network models - Joseph R. Ferrari; Evan L. Preisser; Matthew C. Fitzpatrick (Biological Invasions, 2014)

Biodegradation of ballast tank coating investigated by impedance spectroscopy and microscopy - A. Heyer; F. D’Souza; X. Zhang; G. Ferrari; J. M. C. Mol; J. H. W. de Wit (Biodegradation, 2014)

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

Effects of turbidity and an invasive waterweed on predation by introduced largemouth bass - Maud C. O. Ferrari; Lynn Ranåker; Kelly L. Weinersmith; Matthew J. Young; Andrew Sih; J. Louise Conrad (Environmental Biology of Fishes, 2014)

Background level of risk determines the intensity of predator neophobia in juvenile convict cichlids - Grant E. Brown; Douglas P. Chivers; Chris K. Elvidge; Christopher D. Jackson; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2014)

Spatial models to support the management of coastal marine ecosystems: a short review of the best practices in Liguria, Italy - M. VACCHI; M. MONTEFALCONE; V. PARRAVICINI; A. ROVERE; P. VASSALLO; M. FERRARI; C. MORRI; C. N. BIANCHI (Mediterranean Marine Science, 2013)
Spatial modelling is an emerging approach to the management of coastal marine habitats, as it helps understanding and predicting the results of global change. This paper reviews critically two recent examples developed in Liguria, an administrative region of NW Italy. The first example, aiming at predicting habitat status depending on pressures, provides managers with the opportunity of envisaging different scenarios for the consequences of coastal development choices. The second example defines the status of an important Mediterranean coastal marine habitat (Posidonia oceanica meadows) under natural conditions, allowing for quantifying human impacts on regressed meadows. Both modelling approaches are useful to define the targets of coastal management, and may help choosing the best management option. Well-planned and sustained monitoring is essential to model validation and improvement.

Genetic diversity of the rare and endangered meadow violet ( Viola pumila Chaix) at the southern margin of its range - F. Buldrini; L. Conte; D. Dallai; C. Ferrari (Plant Biosystems, 2013)

Gait analysis in children with cerebral palsy via inertial and magnetic sensors - Josien C. van den Noort; Alberto Ferrari; Andrea G. Cutti; Jules G. Becher; Jaap Harlaar (Medical & Biological Engineering & Computing, 2013)

Retention of acquired predator recognition among shy versus bold juvenile rainbow trout - G. E. Brown; M. C. O. Ferrari; P. H. Malka; L. Fregeau; L. Kayello; D. P. Chivers (Behavioral Ecology and Sociobiology, 2013)

Do fathead minnows, Pimephales promelas Rafinesque, alter their club cell investment in responses to variable risk of infection from Saprolegnia ? - R J Pollock; M S Pollock; M C O Ferrari; S G W Kaminskyj; D P Chivers (Journal of Fish Diseases, 2012)
Fish in the Superorder Ostariophysi possess large epidermal club cells that release chemical cues warning nearby conspecifics of danger. Despite the long‐held assumption that such club cells evolved under the selective force of predation, recent studies demonstrated that predation has no effect on club cell investment. Rather, club cells have an immune function and cell production may be stimulated by skin‐penetrating pathogens and parasites. The current work investigates whether fathead minnows, Pimephales promelas , alter their club cell characteristics based on variation in infection risk. In a 2 × 3 design, we exposed minnows to infective cysts of two oomycete species ( Saprolegnia ferax and S. parasitica ) at three different concentrations (2, 20 or 200 cysts L −1 ). Club cell characteristics (number and size) were quantified 12 days after exposure. Saprolegnia parasitica is thought to be more pathogenic than S. ferax , hence we predicted greater club cell investment and a larger turnover rate of cells by minnows exposed to S. parasitica than S. ferax. We also predicted that minnows exposed to higher numbers of cysts should invest more in club cells and have a higher turnover rate of cells. We found no difference in club cell density or size between fish exposed to the two Saprolegnia species; however, fish exposed to high concentrations of pathogens had smaller club cells than those exposed to low concentrations, indicating a higher rate of turnover of cells in the epidermis.

Intrageneric variation in antipredator responses of coral reef fishes affected by ocean acidification: implications for climate change projections on marine communities - MAUD C. O. FERRARI; DANIELLE L. DIXSON; PHILIP L. MUNDAY; MARK I. McCORMICK; MARK G. MEEKAN; ANDREW SIH; DOUGLAS P. CHIVERS (Global Change Biology, 2011)
Our planet is experiencing an increase in the concentration of atmospheric carbon dioxide (CO 2 ) unprecedented in the past 800 000 years. About 30% of excess atmospheric CO 2 is absorbed by the oceans, thus increasing the concentration of carbonic acid and reducing the ocean's pH. Species able to survive the physiological stress imposed by ocean acidification may still suffer strong indirect negative consequences. Comparing the tolerance of different species to dissolved CO 2 is a necessary first step towards predicting the ecological impacts of rising CO 2 levels on marine communities. While it is intuitive that not all aquatic species will be affected the same way by CO 2 , one could predict that closely related species, sharing similar life histories and ecology, may show similar tolerance levels to CO 2 . Our ability to create functional groups of species according to their CO 2 tolerance may be crucial in our ability to predict community change in the future. Here, we tested the effects of CO 2 exposure on the antipredator responses of four damselfish species ( Pomacentrus chrysurus, Pomacentrus moluccensis, Pomacentrus amboinensis and Pomacentrus nagasakiensis ). Although being sympatric and sharing the same ecology and life history, the four congeneric species showed striking and unexpected variation in CO 2 tolerance, with CO 2 ‐induced loss of response to predation risk ranging from 30% to 95%. Using P. chrysurus as a model species, we further tested if these behavioural differences translated into differential ability to survive predators under natural conditions. Our results indicate that P. chrysurus larvae raised under CO 2 levels predicted by 2070 and 2100 showed decreased antipredator responses to risk, leading to a five‐ to sevenfold increase in predation‐related mortality in the first few hours of settlement. Examining ocean acidification, along with other environmental variables, will be a critical step in further evaluating ecological responses to predicted climatic change.

Methodological characteristics of the national dietary surveys carried out in the European Union as included in the European Food Safety Authority (EFSA) Comprehensive European Food Consumption Database - C. Merten; P. Ferrari; M. Bakker; A. Boss; Á. Hearty; C. Leclercq; O. Lindtner; C. Tlustos; P. Verger; J.L. Volatier; D. Arcella (Food Additives & Contaminants: Part A, 2011)

Intake of aflatoxins through the consumption of peanut products in Brazil - I.C.O. Magrine; S.S.C. Ferrari; G.F. Souza; L. Minamihara; C. Kemmelmeier; E. Bando; M. Machinski (Food Additives & Contaminants Part B-Surveillance, 2011)

Growth rate and retention of learned predator cues by juvenile rainbow trout: faster-growing fish forget sooner - Grant E. Brown; Maud C. O. Ferrari; Patrick H. Malka; Marie-Anne Oligny; Matthew Romano; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2011)

Iron uptake and toxin synthesis in the bloom‐forming Microcystis aeruginosa under iron limitation - Ralitza Alexova; Manabu Fujii; Debra Birch; Jennifer Cheng; T. David Waite; Belinda C. Ferrari; Brett A. Neilan (Environmental Microbiology, 2011)
Summary Toxin production during cyanobacterial blooms poses a significant public health threat in water bodies globally and requires the development of effective bloom management strategies. Previously, synthesis of the hepatotoxin microcystin has been proposed to be regulated by iron availability, but the contribution of the toxin to the adaptation of cyanobacteria to environmental stresses, such as changing light intensity and nutrient limitation, remains unclear. The aim of this study was to compare the iron stress response in toxic and non‐toxic strains of Microcystis aeruginosa subjected to moderate and severe iron limitation. The transcription of a number of genes involved in iron uptake, oxidative stress response, toxin synthesis and transcriptional control of these processes was accessed by quantitative real‐time PCR (qRT‐PCR). The process of adaptation of M. aeruginosa to iron stress was found to be highly dynamic and strain‐specific. Toxin production in PCC 7806 increased in an iron‐dependent manner and appeared to be regulated by FurA. The inability to produce microcystin, either due to natural mutations in the mcy gene cluster or due to insertional inactivation of mcyH , affected the remodelling of the photosynthetic machinery in iron‐stressed cells, the transport of Fe(II) and transcription of the Fur family of transcriptional regulators. The presence of the toxin appears to give an advantage to microcystin‐producing cyanobacteria in the early stages of exposure to severe iron stress and may protect the cell from reactive oxygen species‐induced damage.

Design and preparation of market baskets of European Union commercial baby foods for the assessment of infant exposure to food chemicals and to their effects - R. Piccinelli; M. Pandelova; C. Le Donne; M. Ferrari; K.-W. Schramm; C. Leclercq (Food Additives & Contaminants: Part A, 2010)

Rondon’s Marmoset, Mico rondoni sp. n., from Southwestern Brazilian Amazonia - Stephen F. Ferrari; Leonardo Sena; Maria Paula C. Schneider; José S. Silva Júnior (International Journal of Primatology, 2010)

Genetic diversity and differentiation of three Brazilian populations of Scarlet ibis (Eudocimus ruber) - Evonnildo C. Gonçalves; Stephen F. Ferrari; Tibério César T. Burlamaqui; Leonardo Miranda; Marcelo S. Santos; Artur Silva; Maria Paula C. Schneider (Journal of Ornithology, 2010)

Use of a comprehensive numerical model to improve biventricular pacemaker temporization in patients affected by heart failure undergoing to CRT-D therapy - A. Di Molfetta; L. Santini; G. B. Forleo; M. Cesario; C. Tota; M. Sgueglia; D. Sergi; G. Ferrari; F. Romeo (Medical & Biological Engineering & Computing, 2010)

Anti N1 Cross-Protecting Antibodies Against H5N1 Detected in H1N1 Infected People - E. Frobert; M. Bouscambert-Duchamp; V. Escuret; S. Mundweiler; M. Barthélémy; F. Morfin; M. Valette; C. Gerdil; B. Lina; O. Ferraris (Current Microbiology, 2010)

Comparative Genetic Diversity of Wild and Captive Populations of the Bare-Faced Curassow (Crax fasciolata) Based on Cross-Species Microsatellite Markers: Implications for Conservation and Management - Evonnildo C. Gonçalves; Stephen F. Ferrari; Heitor B. Bastos; Anita Wajntal; Alexandre Aleixo; Maria Paula C. Schneider (Biochemical Genetics, 2010)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Monitoring and assessing old‐growth forest stands by plot sampling - P. Corona; C. Blasi; G. Chirici; L. Facioni; L. Fattorini; B. Ferrari (Plant Biosystems, 2010)

The ghost of predation future: threat-sensitive and temporal assessment of risk by embryonic woodfrogs - Maud C. O. Ferrari; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2010)

The effect of progressive hypoxia on spontaneous activity in single and shoaling golden grey mullet Liza aurata - C. Lefrançois; R. S. Ferrari; J. Moreira da Silva; P. Domenici (Journal of Fish Biology, 2009)
The hypothesis of a differential effect of hypoxia on activity in shoaling v. solitary fish was tested in golden grey mullet Liza aurata . In both solitary and shoaling fish, (1) swimming activity increased significantly at ≤ 60% air saturation compared with normoxia, (2) aquatic surface respiration increased significantly below 15% air saturation and (3) a significant increase in ventilation frequency was observed between 40 and 10% air saturation. Swimming activity was higher in shoaling than in solitary fish, possibly due to social interactions in shoaling fish. Despite showing a higher swimming activity, shoaling individuals showed similar ventilation frequency to the less active solitary fish. This suggests that shoaling exerts a calming effect on L. aurata , probably related to increased safety while in numbers. In addition, shoaling fish spent a higher proportion of time performing aquatic surface respiration at 15% air saturation ( i.e. the highest oxygen level at which aquatic surface respiration was observed) than solitary fish, possibly because of (1) synchronization of aquatic surface respiration in shoaling fish and (2) lower risk of predation perceived by shoaling fish.

Detection of porcine circovirus type 2 (PCV2) from wild boars in central Italy - S. Petrini; S. Barocci; S. Gavaudan; R. Villa; S. Briscolini; M. Sabbatini; C. Mattozzi; F. Barchiesi; S. Salamida; M. Ferrari; M. Paniccià; G. Pezzotti (European Journal of Wildlife Research, 2009)

Dexmedetomidine chemical restraint of two raptor species undergoing inhalation anaesthesia - B. Santangelo; D. Ferrari; I. Di Martino; A. Belli; C. Cordella; A. Ricco; S. Troisi; G. Vesce (Veterinary Research Communications, 2009)

Social context, competitive interactions and the dynamic nature of antipredator responses of juvenile rainbow trout Oncorhynchus mykiss - G. E. Brown; M. C. Harvey; A. O. H. C. Leduc; M. C. O. Ferrari; D. P. Chivers (Journal of Fish Biology, 2009)
The effects of food ration and social context, as well as possible interactions, on the antipredator behaviour of juvenile rainbow trout Onchorhynchus mykiss were investigated in a pair of laboratory studies. In experiment 1, pairs of dominant and subordinate O. mykiss were exposed to conspecific alarm cues when maintained under high or low food rations. Under high food rations, dominant individuals responded to predation risk, whereas subordinates used the opportunity to feed. Under low food ration, however, the opposite pattern was observed, where subordinates responded to predation cues and dominants did not. Experiment 2 consisted of performing the same experiment, however separating the dominant and subordinate O. mykiss 3 h before testing. When tested separately, dominant and subordinate individuals did not differ in their responses to alarm cues, regardless of food ration. These results demonstrate that there is a complex interaction between current energy status and social context on decision making by prey animals.

Threat-sensitive generalization of predator recognition by larval amphibians - Maud C. O. Ferrari; Grant E. Brown; François Messier; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2009)

Abnormal meiosis in tetraploid genotypes ofBrachiaria brizantha (Poaceae) induced by colchicine: its implications for breeding - A. B. Mendes-Bonato; M. Ferrari Felismino; A. M. Souza Kaneshima; C. Pessim; V. Calisto; M. Suely Pagliarini; C. Borges do Valle (Journal of Applied Genetics, 2009)

Applications of flow cytometry in environmental microbiology and biotechnology - Peter L. Bergquist; Elizabeth M. Hardiman; Belinda C. Ferrari; Tristrom Winsley (Extremophiles, 2009)

Establishing physiological blood parameters in the loggerhead sea turtle (Caretta caretta) - D. Gelli; V. Ferrari; A. Zanella; P. Arena; L. Pozzi; S. Nannarelli; C. Vaccaro; D. Bernardini; S. Romagnoli (European Journal of Wildlife Research, 2009)

Sensory complementation and the acquisition of predator recognition by salmonid fishes - Maud C. O. Ferrari; Meaghan A. Vavrek; Chris K. Elvidge; Bryan Fridman; Douglas P. Chivers; Grant E. Brown (Behavioral Ecology and Sociobiology, 2008)

The effect of acute hypoxia on swimming stamina at optimal swimming speed in flathead grey mullet Mugil cephalus - M. Vagner; C. Lefrançois; R. S. Ferrari; A. Satta; P. Domenici (Marine Biology, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Predator-induced changes in morphology of a prey fish: the effects of food level and temporal frequency of predation risk - Douglas P. Chivers; Xiaoxia Zhao; Grant E. Brown; Tracy A. Marchant; Maud C. O. Ferrari (Evolutionary Ecology, 2008)

Threat-sensitive learning of predators by larval mosquitoes Culex restuans - Maud C. O. Ferrari; François Messier; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2008)

Closed-tube DNA extraction using a thermostable proteinase is highly sensitive, capable of single parasite detection - B. C. Ferrari; M. L. Power; P. L. Bergquist (Biotechnology Letters, 2007)

Adult Stem Cells: Perspectives for Therapeutic Applications - M. Ferrari; A. Corradi; M. Lazzaretti; M. De’Cillà; C. G. Losi; R. Villa; A. Lanfranchi (Veterinary Research Communications, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Alcohol intake and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition (EPIC) - Anne Tjønneland; Jane Christensen; Anja Olsen; Connie Stripp; Birthe L. Thomsen; Kim Overvad; Petra H. M. Peeters; Carla H. van Gils; H. Bas Bueno-de-Mesquita; Marga C. Ocké; Anne Thiebaut; Agnès Fournier; et al. (Cancer Causes & Control, 2007)

Interactions between tayras (Eira barbara) and red-handed howlers (Alouatta belzebul) in eastern Amazonia - Carolina C. Camargo; Stephen F. Ferrari (Primates, 2007)

Imported malaria at Italy’s National Institute for Infectious Diseases Lazzaro Spallanzani, 1984–2003 - F. Spinazzola; E. Nicastri; C. Vlassi; P. Ghirga; M. Marco; S. Pittalis; M. G. Paglia; C. Ferrari; P. Narciso (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

The dynamic nature of antipredator behavior: prey fish integrate threat-sensitive antipredator responses within background levels of predation risk - Grant E. Brown; Alix C. Rive; Maud C. O. Ferrari; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2006)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

The role of learning in the acquisition of threat-sensitive responses to predator odours - Maud C. O. Ferrari; Terence Capitania-Kwok; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2006)

The Complete Nucleotide Sequence and Genomic Organization of Citrus Leprosis Associated Virus, Cytoplasmatic type (CiLV-C) - Renata C. Pascon; João Paulo Kitajima; Michèle C. Breton; Laura Assumpção; Christian Greggio; Almir S. Zanca; Vagner Katsumi Okura; Marcos C. Alegria; Maria E. Camargo; Giovana G.C. Silva; Jussara C. Cardozo; Marcelo A. Vallim; et al. (Virus Genes, 2006)

Nanometric modulation in apatite - C. Ferraris; T. J. White; J. Plévert; R. Wegner (Physics and Chemistry of Minerals, 2005)

Study on the Virulence, Cell-mediated Immune Response and Histolesivity of Three Field PRRSV Strains with an ORF 5 Genetic Variation - A. Corradi; M. Ferrari; A. M. Cantoni; C. Robotti; L. Alborali; R. Di Lecce; P. Candotti; G. P. Sandri; P. Borghetti (Veterinary Research Communications, 2005)

Vaccination Trials Against Bovine Herpesvirus-1 - G. Castrucci; M. Ferrari; D. Salvatori; S. Sardonini; F. Frigeri; S. Petrini; M. Lo Dico; C. Marchini; A. Rotola; A. Amici; M. Provinciali; A. Tosini; et al. (Veterinary Research Communications, 2005)

X-linked heterochromatin distribution in the holocentric chromosomes of the green apple aphid Aphis pomi - A. Criniti; G. Simonazzi; S. Cassanelli; M. Ferrari; D. Bizzaro; G. C. Manicardi (Genetica, 2005)

Recognition and signalling in the cell wall: The case of endopolygalacturonase, PGIP and oligogalacturonides - B Mattei; R Galletti; C Manfredini; D Pontiggia; G Salvi; S Spadoni; C Caprari; S Ferrari; D Bellincampi; F Cervone; G De Lorenzo (Plant Biosystems, 2005)

Evaluation of Endogenous Pig Retrovirus Expression and of Tumorigenicity in Nude Mice - M. Ferrari; A. Corradi; P.G. Petronini; A. Tosini; A. Toniolo; C. Robotti; R. Moratti (Veterinary Research Communications, 2004)

Sigmoidal exsolution by internal shear stress in pyroxenes from chondritic meteorites - C. Ferraris; L. Folco; M. Mellini (Physics and Chemistry of Minerals, 2003)

Geophagy as a Correlate of Folivory in Red-Handed Howler Monkeys (Alouatta belzebul) from Eastern Brazilian Amazonia - Luciane L. de Souza; Stephen F. Ferrari; Marcondes L. da Costa; Dirse C. Kern (Journal of Chemical Ecology, 2002)

Is a Kit for Identification of Clinical Yeasts Correctly Evaluated When Released onto the Market? - A. M. Tortorano; F. Barchiesi; E. Manso; M. T. Montagna; C. Farina; L. Ferrari; A. Raballo; A. Grancini; G. Lombardi (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

An artificial grasping evaluation system for the paralysed hand - M. C. Ferrari de Castro; A. Cliquet (Medical & Biological Engineering & Computing, 2000)

Titi monkeys (Callicebus spp., Atelidae: Platyrrhini) in the Brazilian state of Rondônia - Stephen F. Ferrari; Simone Iwanaga; Mariluce R. Messias; Eleildon M. Ramos; Paulo C. S. Ramos; Ernesto H. da Cruz Neto; Paulo E. G. Coutinho (Primates, 2000)

Zoogeography of Chiropotes albinasus (Platyrrhini, Atelidae) in Southwestern Amazonia - Stephen F. Ferrari; Simone Iwanaga; Paulo E. G. Coutinho; Mariluce R. Messias; Ernesto H. Cruz Neto; Eleildon M. Ramos; Paulo C. S. Ramos (International Journal of Primatology, 1999)

Distribution of microbial assemblages in the Central Arctic Ocean Basin studied by PCR/DGGE: analysis of a large data set - V. C. Ferrari; J. T. Hollibaugh (Hydrobiologia, 1999)

Effects of a short-term strength training programme on lymphocyte subsets at rest in elderly humans - S. Bermon; P. Philip; P. Ferrari; M. Candito; C. Dolisi (European Journal of Applied Physiology, 1999)

Acetylcholinesterase assay may predict cognitive response of Alzheimer patients to eptastigmine treatment - B. P. Imbimbo; M. Nicoli; C. Martini; G. P. Tomelleri; P. Martelli; G. P. Ferrari; G. Gambina (European Journal of Clinical Pharmacology, 1998)

Electrophoretic Polymorphisms and Their Taxonomic Implications in Callitrichini (Primates, Platyrrhini) - C. M. Meireles; J. Czelusniak; I. Sampaio; H. Schneider; S. F. Ferrari; A. F. Coimbra-Filho; A. Pissinatti; J. A. P. C. Muniz; H. S. Ferreira; M. P. C. Schneider (Biochemical Genetics, 1998)

Changing Concentrations of Cu, Zn, Cd and Pb in a High Altitude Peat Bog from Bolivia during the Past Three Centuries - E. Espi; C.F. Boutron; S. Hong; M. Pourchet; C. Ferrari; W. Shotyk; L. Charlet (Water, Air, & Soil Pollution, 1997)

Cytogenetic biomonitoring of styrene-exposed plastic boat builders - M. Artuso; G. Angotzi; S. Bonassi; S. Bonatti; M. De Ferrari; D. Gargano; L. Lastrucci; L. Miligi; C. Sbrana; A. Abbondandolo (Archives of Environmental Contamination and Toxicology, 1995)